A New Series of Indeno[1,2-c]pyrazoles as EGFR TK Inhibitors for NSCLC Therapy - Ahmet Özdemir; Halilibrahim Ciftci; Belgin Sever; Hiroshi Tateishi; Masami Otsuka; Mikako Fujita; Mehlika Dilek Altıntop (Molecules, 2022)
Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related death throughout the world. Due to the shortcomings of traditional chemotherapy, targeted therapies have come into prominence for the management of NSCLC. In particular, epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) therapy has emerged as a first-line therapy for NSCLC patients with EGFR-activating mutations. In this context, new indenopyrazoles, which were prepared by an efficient microwave-assisted method, were subjected to in silico and in vitro assays to evaluate their potency as EGFR TK-targeted anti-NSCLC agents. Compound 4 was the most promising antitumor agent towards A549 human lung adenocarcinoma cells, with an IC50 value of 6.13 µM compared to erlotinib (IC50 = 19.67 µM). Based on its low cytotoxicity to peripheral blood mononuclear cells (PBMCs), it can be concluded that compound 4 exerts selective antitumor action. This compound also inhibited EGFR TK with an IC50 value of 17.58 µM compared to erlotinib (IC50 = 0.04 µM) and induced apoptosis (56.30%). Taking into account in silico and in vitro data, compound 4 stands out as a potential EGFR TKI for the treatment of NSCLC.